PERBAIKAN PERFORMA MESIN AUTOMATIC VEHICLE DENGAN FUEL-BOOSTER RACING - Sukendro Sasongko; Titik Arlisa; Hery Irawan (Jurusan Teknik Mesin Universitas Negeri Surabaya, 2023)
The performance enhancing engine of automatic vehicle experimentally investigated by adding a fuel-booster. The study aims to improve the combustion matic engine Honda by adding the fuel addictive reactant. The existence of fuel-addictive reactants enhances engine combustion. Besides that, the high octane number of fuel could be optimized during chemical reactions. Thus, the study investigates the matic motorcycle engine at steady operation. The experiment methods vary the fuel additive concentration. The fuel addictive varied is Eco racing to percentile. Thus, the engine performed by varying sparks (racing spark and standard spark). The engine of matic motorcycle is investigated. The engine performance is studied at the stand dyno test. The specific fuel consumption is scaled by a litre of Pertalite. The gas emissions were probed by a gas analyser. The investigation is conducted by three time replication. The result shows the fuel-addictive reactant (Eco racing) performs the best contributions during an iridium spark installed at the engine. Thus, the engine power was detected at 7,5 Hp. Torque resulted by 26,68 Nm; specific fuel consumption was at 0,048 gram,/Hp.s. Engine-Rpm of 6000 emits CO 0,27%, HC 147 ppm, CO2 12,0 %, dan O2 20,84 %. Those gas concentrations are still lower and acceptable due to their concentration being lower than that in the national emissions standard.